A comparative study of anti-inflammatory properties and activities of green and red Christia vespertilionis leaves - Izzah Farhah Zambari,; Nur Airina Muhamad,; Sitti Rahma Abdul Hafid, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Christia vespertilionis is a plant traditionally used to treat various diseases, including inflammation. This study aims to compare and analyze the anti-inflammatory properties and activities of green and red C. vespertilionis leaves and to determine the correlation between the protease inhibition assay and phenolic content. Preliminary phytochemical analysis showed the presence of alkaloids, tannins, saponins, cardenolides, phenolics, cardiac glycosides, flavonoids, and steroids in green and red leaves. Green leaf had the highest anti-inflammation potential, with a high extraction yield (6.39 ± 0.01%), phenolic content (29.25 ± 0.50 mg) gallic acid equivalent [GAE]/mL), flavonoid content (1.57 ± 0.03 mg quercetin acid equivalent [QE]/mL) and tannin content (22.70 ± 3.15 mg tannic acid equivalent [TAE]/mL). Green leaf contained more anti-inflammatory compounds, including n-hexadecanoic acid, phytol, 9, 12, 15-octadecatrienoic acid (Z, Z, Z)- and squalene. The protease inhibition assay showed that green leaf had anti-inflammatory activity at 66.55 ± 2.59% with the half-maximal inhibitory concentration (IC50) of 284.59 ± 10.63 μg/mL. The green leaf showed a significant positive correlation between the protease inhibition assay and phenolic content, with R2 = 0.6821. We conclude that both green and red C. vespertilionis types have the potential to act as anti-inflammatory agents, but green leaves are preferable.